2006
DOI: 10.1007/s00330-005-0034-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of surgically excluded popliteal artery aneurysms with multi-slice CT angiography and Doppler ultrasound

Abstract: The purpose of this study was to evaluate the role of multi-slice computed tomography (MSCT) angiography in the follow-up of popliteal artery aneurysms (PAAs) that have been operated on. Aneurysm exclusion and progression, graft patency and graft-related complications were analyzed. Fourteen patients with 21 surgically excluded PAAs were evaluated with MSCT angiography with slice thickness of 1.25 mm. The mean follow-up time was 67 months. MSCT demonstrated blood flow in six nonexcluded PAAs (24%), with an ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Despite improvements in vascular surgical techniques, popliteal vascular injuries and popliteal aneurysms continue to be potentially dangerous lesions with high percentage of leg amputations. [14][15][16] This study state right popliteal arteries are slightly larger (4.9 ± 0.7 mm) as compare to left popliteal artery (4.8± 0.5 mm). This study also reconfirm popliteal arteries of men are slightly larger than that of female (4.9 ± 0.7 mm), (4.6± 0.9 mm) and left popliteal artery (4.8± 0.5 mm), (4.6± 0.7 mm) respectively.…”
Section: Discussionmentioning
confidence: 49%
“…Despite improvements in vascular surgical techniques, popliteal vascular injuries and popliteal aneurysms continue to be potentially dangerous lesions with high percentage of leg amputations. [14][15][16] This study state right popliteal arteries are slightly larger (4.9 ± 0.7 mm) as compare to left popliteal artery (4.8± 0.5 mm). This study also reconfirm popliteal arteries of men are slightly larger than that of female (4.9 ± 0.7 mm), (4.6± 0.9 mm) and left popliteal artery (4.8± 0.5 mm), (4.6± 0.7 mm) respectively.…”
Section: Discussionmentioning
confidence: 49%
“…Popliteal artery is having considerable importance in various diagnostic and therapeutic procedures in the world of healthcare such as bypass surgery, transluminal angioplasty and sub intimal angioplasty. Popliteal aneurismal and vascular injuries proceeded to be extremely dangerous leads to high percentage of leg amputations 11,12 Various researchers like Thomas Sandgren et al 13 Zuhal et al 14 Morris-stiff et al 15 and Debasso et al 16 measured the mean diameter of the popliteal artery was 7.4 mm ± 0.9., 7.5 mm ±1.3, 7.4 ± 1.3 mm and 7.4 mm respectively in their study. This was the higher value in comparison to our study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research already reported that collateral geniculate arteries exist and can cause sac growth in excluded PAA but also prevent lower limb ischemia in case of an occlusion. 35,36 There are a number of limitations to this study, including the retrospective design and the relatively small sample size. Only patients both treated and followed up in our vascular center were included in this study.…”
Section: Discussionmentioning
confidence: 99%